The Pathobiome of Salmo trutta From the North Sea to the Barents Sea - Robert J. Lennox; Kristina M. Miller; Abdullah Madhun; Angela D. Schulze; Sindre Håvarstein Eldøy; Trond E. Isaksen; Rune Nilsen; Dylan Shea; Kim Birnie‐Gauvin; Jan Grimsrud Davidsen; Steven J. Cooke; Knut Wiik Vollset (Journal of Biogeography, 2025)
Aim Salmonids are some of the best studied species with respect to their pathobiome, and at the northern range limit, there is potential for pathogens to expand with both climate change and increased fish farming in the north. Location We sampled sea‐run brown trout from throughout Norway for gill tissue and conducted both pooled and individual screenings for a total of 47 pathogens. Time Period Samples were collected during spring in 2020 and 2021. Major Taxa Bacteria, viruses and parasites of sea‐run brown trout. Methods Brown trout were gill biopsied as part of the national sea lice monitoring programme and samples were sent for laboratory analysis using the Fluidigm system, which screened for a broad panel of different pathogenic species. Results Permutated multivariate analysis of variance revealed that the pathobiome richness of trout was more related to latitude than to fish farming biomass in the region where samples were taken. However, non‐metric multidimensional scaling revealed a significant association between the individual pathobiome and the number of copepodid‐stage Lepeophtheirus salmonis lice, which did reveal a south/central versus northern Norway segregation in pathogen distributions. Importantly, many pathogens positively associated with sea lice in southern/central Norway are known to be carried, and potentially transmitted by sea lice. Main conclusions In northern Norway, pathogens normally associated with infection and disease in trout were more commonly observed. However, given that most pathogens were detected from southern to northern Norway, it appears that further expansion of farms in the north are not likely to lead to further introductions of pathogens into northern areas of Norway, although it could amplify the prevalence of these pathogens on wild salmon.

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.